Fatal outcome related risks in severely malnourished children with pneumonia in an urban critical care ward of Bangladesh (Bangladesh Critical Care Journal, 2013)
Background: Fatal outcome related risks are high when children with pneumonia present with severe acute malnutrition (SAM). However, data are limited on fatality related risk factors from pneumonia in Children with SAM especially those who attended in critical care ward. We evaluated clinically identifiable risks for fatal outcome in under-five Children with SAM with pneumonia at a critical care ward in an urban hospital. Methods: This study was of unmatched case-control design and Children with SAM of either sex, aged 0-59 months, admitted to the Intensive Care Unit (ICU) of Dhaka Hospital of the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b) from April 2011 through July 2012 with radiological pneumonia were studied. The study children who had fatal outcome constituted the cases (n=35), and randomly selected children who survived constituted the controls (n=105). Results: The age (months) among the cases and the controls [median (inter-quartile range)] was comparable [8.0 (4.9, 11.0) vs. 9.7 (5.0, 18.0); p=0.210)]. In multivariate logistic regression analysis, after adjusting for potential confounders, such as abnormal mental status, vomiting, and systolic hypotension (